Border control and accident rate of irregular immigration in the route to the Canary Islands (Spain) during the COVID-19 pandemic - Mesa-Pérez, Carmelo Ulises; Parreño-Castellano, Juan Manuel; Domínguez-Mujica, Josefina (Hungarian Geographical Bulletin, 2023)
Throughout the first decades of the 21st century, the maritime borders of the European Union have witnessed a growing and increasingly complex mobility of an irregular nature. Moreover, the effects of the COVID-19 crisis on many African countries revealed the weakness of the maritime border and its permeability, as well as its increased danger. This research aims to study these irregular migration flows by sea during 2020 and 2021, through the Atlantic border between the Canary Islands and Africa. The so-called “Canary route” is one of the most dangerous maritime routes in the world due to the ocean conditions, the distances that must be covered and the way in which migrants move. Our analysis will therefore focus on one of the central aspects of this crossing, its danger and associated accident rate, which can be measured in terms of the number of shipwrecks, deaths, and missing persons. The objectives of this paper are: i) to show the spatial location of those wrecks; ii) to give an estimate of data on missing persons and deaths; iii) to focus on the study of those persons affected; iv) to delve into the underlying causes; and v) to analyse the border control actions developed during the pandemic. With this aim, information has been compiled from different national and international sources: official records, contrasted data provided by some NGOs and the IOM, and testimonies of the agents involved. This material is used to reflect on the normalization of border control as a factor that inevitably leads to deaths and disappearances. It suggests that this event should be a central element in European migration policy, contributing to designing border control actions that go beyond containment, thereby preventing the loss of human lives.